RELATIONSHIP OF REFRACTION CLAIMS WITH STUDENT ACHIEVEMENT IN SMP NEGERI PADANG CITY - Febry Corina; Peni Okto Randi; Rina Novalinda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Vision problems related to the learning process include deficits in efficiency and processing of visual information that have the potential to interfere with a person's ability to learn. The purpose of this study was to determine the relationship between refractive errors and student achievement. This type of research is descriptive quantitative. The population in this study was 30 adolescents at SMP Negeri Padang City. The discussion is sorted according to the formulation of the problem. Based on the results of the study, it was found that 33.3% of the students had refractive errors myopia. In addition, there is a significant relationship between refractive errors and student achievement at SMP Negeri Padang City. Students who feel that their vision is blurry to see far away should immediately check their eyes and also have to be careful about the characteristics of myopia disorders and other refractive errors. It is recommended that students who have wrong reading habits pay more attention to their eye health so that unwanted things do not occur.